The 1Malaysia amongst us - Abd Razak, Dzulkifli (2009)
THE observation that Sabah and Sarawak are living examples of the 1Malaysia concept cannot get a better endorsement than from the prime minister himself. Datuk Seri Najib Razak described the spirit of unity in these two states as the coming together of "many things that unite us, instead of allowing the few things that divide us to drive us apart". "Malaysians of any race or creed need simply look to Sabah and Sarawak to gain an understanding of the incredibly strong and harmonious unity that can be found in accepting and respecting the diversity of our nation."